General Aspects of Two-Component Regulatory Circuits in Bacteria: Domains, Signals and Roles - Padilla-Vaca, Felipe; Mondragón-Jaimes, Verónica; Franco, Bernardo (Current protein & peptide science, 2017)
All living organisms are subject to changing environments, which must be sensed in order to respond swiftly and efficiently. Two-component systems (TCS) are signal transduction regulatory circuits based typically on a membrane bound sensor kinase and a cytoplasmic response regulator, that is activated through a histidine to aspartate phosphorelay reactions. Activated response regulator acts usually as a transcription factor. The best known examples were identified in bacteria, but they are also found in fungi, algae and plants. Thus far, they are not found in mammals. Regulatory circuits coupled to two-component systems exhibit a myriad of responses to environmental stimuli such as: redox potential, pH, specific metabolites, pressure, light and more recently to specific antimicrobial peptides that activate a sensor kinase responsible for expressing virulence factors through the active response regulator. In this review we explore general aspects on two-component systems that ultimately can play a role on virulence regulation, also the intriguing domain properties of the sensor kinases that can be a potential target for antimicrobial compounds. Only a handful of sensor kinases are extensively characterized, the vast majority belong to what we call 'the dark matter of bacterial signal transduction' since no known signal, structure and biochemical properties are available. Regulatory circuits from vertebrate pathogenic organisms can explain virulence in terms of either response to environmental factors or specific niche occupancy. Hopefully, knowledge on these signal transduction systems can lead to identify novel molecules that target two-component systems, since the increase of drug resistant microorganisms is worrisome.